2004
DOI: 10.1124/dmd.32.2.178
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Hydroxylamine Glucuronide Metabolite of an Oral Hypoglycemic Agent

Abstract: This article is available online at http://dmd.aspetjournals.org ABSTRACT:Glucuronides of piperazine hydroxylamines are rarely reported in the literature, and even more rarely are their structures unambiguously identified. One major metabolite was detected by liquid chromatography/mass spectrometry-radioactivity in urine from monkeys treated with the aryl piperazine oral hypoglycemic agent 9-[(1S,2R)-2-fluoro-1-methylpropyl]-2-methoxy-6-(1-piperazinyl) purine hydrochloride (1). The mass spectrum of this metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 14 publications
3
21
1
Order By: Relevance
“…The ions at m/z 315, 299, 298, and 240 for 4 and 299, 298, 256, and 240 for 3 correspond to the loss of a glucuronic acid moiety (m/z 315), loss of a glucuronic acid moiety and oxygen (m/z 299), and loss of an O-glucuronic acid moiety and fragmentation of the piperazine ring (m/z 240 and 256). This pattern is consistent with the fragmentation of glucuronic acid conjugate metabolites of a monooxygenated piperazine derivative (Delbressine et al, 1992;Schaber et al, 2001;Miller et al, 2004). Analysis of the (bio)synthesized standards containing 3 and 4 using MicrOTOF MS showed the compounds to have exact mass values of 491.18608 and 491.18325, respectively.…”
Section: Resultssupporting
confidence: 63%
See 3 more Smart Citations
“…The ions at m/z 315, 299, 298, and 240 for 4 and 299, 298, 256, and 240 for 3 correspond to the loss of a glucuronic acid moiety (m/z 315), loss of a glucuronic acid moiety and oxygen (m/z 299), and loss of an O-glucuronic acid moiety and fragmentation of the piperazine ring (m/z 240 and 256). This pattern is consistent with the fragmentation of glucuronic acid conjugate metabolites of a monooxygenated piperazine derivative (Delbressine et al, 1992;Schaber et al, 2001;Miller et al, 2004). Analysis of the (bio)synthesized standards containing 3 and 4 using MicrOTOF MS showed the compounds to have exact mass values of 491.18608 and 491.18325, respectively.…”
Section: Resultssupporting
confidence: 63%
“…Organic synthesis of 4 was unsuccessful, but in vitro biosynthesis using human liver microsomes, UDPGA, alamethicin (antibiotic, precautionary measure) and saccharic acid lactone (␤-glucuronidase inhibitor, precautionary measure) (Miller et al, 2004;Picard et al, 2005;Bowalgaha et al, 2007;Wen et al, 2007a,b;Hintikka et al, 2008) and subsequent semipreparative HPLC-MS resulted in the production of approximately 10 mg of the metabolite 4. During evaporation of the fractions collected during semipreparative HPLC-MS, 4 started precipitating and was collected in sufficiently pure form for one-and two-dimensional NMR experiments.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, because of the significance of M5 in monkeys reported herein, LC/MS/NMR analyses of nonradiolabeled M5 purified from the urine of a monkey administered 1 unequivocally identified M5 as an N-O-glucuronide of 1, consistent with the mechanistic structural rationalization of fragment ions within its product ion spectrum (Fig. 3) and previously characterized alicyclic N-O-glucuronides (Straub et al, 1988;Delbressine et al, 1992;Edlund and Baranczewski, 2004;Miller et al, 2004). In particular, the 1 H spectrum of M5 clearly showed the anomeric proton signal (4.37 ppm) of the glucuronide moiety, whereas the correlation spectroscopy spectrum indicated that this was the most downfield resonance in a five-proton spin system that terminated with a doublet at 3.59 ppm.…”
Section: Excretion Of Total Radioactivity In Monkeysmentioning
confidence: 59%